Rhesus Macaque Activating Killer Immunoglobulin-Like Receptors Associate With Fc Receptor Gamma (FCER1G) and Not With DAP12 Adaptor Proteins Resulting in Stabilized Expression and Enabling Signal Transduction - Hasan, Mohammad Zahidul; Walter, Lutz (Frontiers in Immunology, 2021)
Activating killer cell immunoglobulin-like receptors (KIR) in macaques are thought to be derived by genetic recombination of the region encoding the transmembrane and intracellular part of KIR2DL4 and a KIR3D gene. As a result, all macaque activating KIR possess a positively charged arginine residue in the transmembrane region. As human KIR2DL4 associates with the FCER1G (also called Fc receptor-gamma, FcRγ) adaptor, we hypothesized that in contrast to human and great ape the activating KIRs of macaques associate with FcRγ instead of DAP12. By applying co-immunoprecipitation of transfected as well as primary cells, we demonstrate that rhesus macaque KIR3DS05 indeed associates with FcRγ and not with DAP12. This association with FcRγ results in increased and substantially stabilized surface expression of KIR3DS05. In addition, we demonstrate that binding of specific ligands of KIR3DS05, Mamu-A1*001 and A1*011, resulted in signal transduction in the presence of FcRγ in contrast to DAP12.